EVALUASI LAYANAN SHELTER DAN TINGKAT PENGISIAN BUS TRANS METRO BANDUNG KORIDOR CICAHEUM-CIBEUREUM - Oktano, Luthfi Yudha; Joewono, Tri Basuki (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Quality of service of public transportation is determined also by the quality of stop (shelter). The analysis is needed to evaluate the effect to load factor. The aim of this study is to evaluate the quality of service of shelter and to determine the suggestion of additional shelter using ArcGIS software.The results of the service definition in digital map are analyzed to evaluate its concentration and effects. The study results suggest 11 additional location for shelter with 500 m catchment area. This is the most effective location based on the analysis of bus stop performance and load factor. The analysis based on 500 m catchment area results load factor as much as 0,90 psr/space of load factor and the average distance between stops is 801,09 m.